First parallax measurements toward a 6.7 GHZ methanol maser with the Australian long baseline array - Distance to G 339.884-1.259 - Krishnan, V.; Ellingsen, S.; Reid, M.; Brunthaler, A.; Sanna, A.; McCallum, J.; Reynolds, C.; Bignall, H.; Phillips, C.; Dodson, R.; Rioja, M.; Caswell, J.; et al. (Institute of Physics Publishing, 2015)
© 2015. The American Astronomical Society. All rights reserved. We have conducted the first parallax and proper motion measurements of 6.7 GHz methanol maser emission using the Australian Long Baseline Array. The parallax of G 339.8841.259 measured from five epochs of observations is 0.48 ± 0.08 mas, corresponding to a distance of - 2.1+0.4 -0.3 kpc, placing it in the Scutum spiral arm. This is consistent (within the combined uncertainty) with the kinematic distance estimate for this source at 2.5 ± 0.5 kpc using the latest Solar and Galactic rotation parameters. We find from the Lyman continuum photon flux that the embedded core of the young star is of spectral type B1, demonstrating that luminous 6.7 GHz methanol masers can be associated with high-mass stars toward the lower end of the mass range.